Evaluation of SNPs of G6PD, with regard to the 3D conformational, structural and stability alterations, in order to investigate the clinical implications and potential applications - Sanabria, Natasha Mary-Anne (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2019)
Expected release date-April 2020
Keywords: Uncatalogued